Effectiveness of Flashcard Media on the Increase of Vocabulary at School: Efektivitas Media Flashcard terhadap Peningkatan Mufradat di MTs Muhammadiyah 1 Taman - Arvira Pramita Harlan; Khizanatul Hikmah (Universitas Muhammadiyah Sidoarjo, 2022)
Mufradat or vocabulary is the basic thing that needs to be mastered in learning Arabic. Many students have difficulty understanding Arabic because of the low Mufradat mastered. To improve the mastery of Mufradat, researchers are interested in applying one of the learning media in the form of Flashcards and to determine the effectiveness of using Flashcards as an effort to increase Mufradat in MTs Muhammadiyah 1 Taman. This study uses quantitative research with experimental methods, using Pre-Experimental Design in the form of One Group Pretest-Posttest Design. Collecting data in this study using the methods of observation, interviews, tests and documentation. The results of this study indicate that the application of Flashcard media in learning is carried out by demonstration and quiz methods. After demonstrating the Flashcard, the teacher does individual and group quizzes. This is evidenced by the results of the t-test analysis where tcount 11,585 > ttable 2.052 means that H1 is accepted.